HEAVY METALS (CHROMIUM, COPPER, LEAD, AND ALUMINUM) ON SOME BIOCHEMICAL PARAMETERS IN SACCHAROMYCES CEREVISIAE CULTURE MEDIUM - Kirecci, Oguz Ayhan; Ozsahin, Ayse Dilek; Yilmaz, Okkes; Erdem, Figen; Sarigul, Halise (Parlar Scientific Publications (P S P), 2017)
Concept of heavy metal is used as toxic or toxic metal. Heavy metals are effective at high density and low concentrations. In some systems, the action mechanism of heavy metals depends on the concentration. Effects of heavy metal vary depending on the nature of the species and metal ions. In the complex organisms or yeast, the effects of microelements are often the research subject in recent years. In addition to preventing the disease effect of heavy metals (such as chromium, copper, chromium, lead and aluminum) in animal and human metabolism, their effects on yeast metabolism are the subject of scientific studies. This study revealed the effects of heavy metal (chromium, lead, copper, and aluminum) toxicity on MDA, fatty acids, vitamin, and phytosterols in S. cerevisiae. In addition, this study demonstrated the effects of heavy metal toxicity on antioxidant systems and removal of heavy metal toxicity in S. cerevisiae via antioxidant systems which have a great importance in the removal of heavy metal toxicity. All living organisms should avoid these heavy metals. Especially, the increase of MDA levels showed that accumulation of heavy metals caused the severe damage in all living cells. It is difficult to explain the principles of the antioxidant defense system in living organisms and antioxidant defense system is affected by environmental changes. Therefore, different results were obtained in S. cerevisiae cells. The results of the present study showed that the different heavy metals had different effects on antioxidant defense system.
Keywords: Saccharomyces cerevisiae; Heavy Metal; MDA; Fatty Acid; Vitamin; Antioxidant Systems